Incidence of enteroparasites in fish from three tributaries of the Madeira River: A Unique Health issue in Rondônia, Brazil (Research, Society and Development, 2022)
The Fish is considered an important food source for Amazonian populations, however anthropic actions have promoted a diversity of zoonotic parasites. The objective of this study was to identify the enteroparasitic fauna in fecal samples of fish residing in the tributaries of the Madeira River, in Rondônia, Brazil. In this experimental research, there were collections of the intestine of captured fishes with gilnets between the periods of July 2021 and June 2022. Four collections were carried out: two in the creek Mutum Paraná, one in the creek Belmont and one in the creek Araras. For each collection point, 10 specimens were examined, totaling 40 fish. Fecal parasitological analysis was performed using two concomitant techniques, a spontaneous sedimentation method (Hoffman) and a density fluctuation method (Willis), allowing the identification of heavy and light microorganisms. The samples were morphologically analyzed by optical microscopy at 100 and 400X magnifications, allowing the identification of 13 genera of parasites: Taenia sp., Hymenolepis sp., Entamoeba sp, Capillaria sp., Toxocara sp., Strongyloides sp., Ascaris sp., Doradamphistoma sp., Dadaytrema sp., Hysterothylacium sp., Enterobius sp., Balantidium sp. and Ancylostoma sp. It is concluded that the fish collected in the affluents of the study presented several zoonotic parasites. The wide presence of these parasites makes it essential to adopt sanitary measures in post-slaughter management, as well as care in the disposal of viscera and food preparation in order to avoid contamination.